Date palm transcriptome analysis provides new insights on changes in response to high salt stress of colonized roots with the endophytic fungus Piriformospora indica - Ahmad, Manzoor; Abdul Aziz, Mughair; Sabeem, Miloofer; Kutty, M. Sangeeta; Sivasankaran, Sathesh K.; Brini, Faical; Xiao, Ting Ting; Blilou, Ikram; Masmoudi, Khaled (Frontiers in Plant Science, 2024)
Salinity is a significant threat that causes considerable yield losses in date palm. The root endophytic fungus Piriformospora indica has proven effective in providing salt stress tolerance to host plants. However, the underlying molecular mechanism facilitating the date palm's response to P. indica inoculation, and its involvement for in the salt stress tolerance tolerance, remains unknown. In this study, the colonization of P. indica on date palm seedlings exposed to saline conditions was observed through confocal microscopy, and its impact on gene expressions was evaluated using the transcriptomic analysis. Our findings indicate show that P. indica colonization reinforced the cortical cells, prevented them from plasmolysis and cell death under salinity. The RNAseq analysis produced clean reads ranging from 62,040,451 to 3,652,095 across the treatment groups, successfully assembling into 30,600 annotated genes. Out of them, the number of differentially expressed genes (DEGs) varied across the treatments: i.e., 2523, 2031, and 1936 DEGs were upregulated, while 2323, 959, and 3546 were downregulated in Salt, Fungi, and Fungi+Salt groups, respectively. Furthermore, principal component analysis (PCA) based on transcriptome profiles revealed discrete clustering of samples from different treatment groups. KEGG and GO pathways enrichment analysis highlighted variation in the number and types of enriched pathways among the treatments. Our study indicated variations in gene expression related to plant hormone biosynthesis and signal transduction (auxin, abscisic acid, gibberellin, and ethylene), ABC transporters, sodium/hydrogen exchanger, cation HKT transporter, transcription factors such as WRKY and MYBs, and the plant immune system (lipoxygenase and jasmonate) of the date palm seedlings. By characterizing the transcriptome of date palm roots under salt stress and with colonization of P. indica, the present findings provide valuable perspectives into on the molecular mechanisms responsible for inducing salinity stress tolerance in plants.